Pre-infection Mechanisms on the Phylloplane: The First Biochemical Battlefield Between the Cacao Tree and Witches' Broom Pathogen - Zugaib, Maria; Almeida, Dayanne Silva Monteiro de; de Santana, Monique Reis; Macêdo Ferreira, Monaliza; Santana, Juliano Oliveira; Mangabeira, Pedro Antônio Oliveira; Souza, Jorge Teodoro de; Pirovani, Carlos Priminho (Frontiers in Agronomy, 2022)
The leaf surface has secreted biochemical substances and pre-existing morphological structures, as well as the presence of microorganisms. This dynamic environment constitutes a plant´s initial defense, as well as the first contact of phytopathogens during invasion. Spore germination starts on the phylloplane and is a fundamental process for fungal development, and hence the establishment of disease. In this review, we address the phylloplane’s innate defense mechanisms and biochemical reactions involved in the early stage of phytopathogenic fungal development. The focus is synthesize the pre-infection molecular and biochemical processes of the interaction between Theobroma cacao and Moniliophthora perniciosa, presenting how the defense mechanisms of the phylloplane can act to inhibit the protein involved at the beginning of fungal spore germination. We conclude that the phylloplane of the cocoa resistant genotype to M. perniciosa has preformed chemical compounds, pre-existing morphological structures and the presence of microorganisms that participate in the pre-infection defense of the plant. Also, the inhibition of proteins involved in the germination mechanism of M. perniciosa basidiospores by chemical and structural compounds present in the cocoa phylloplane may decrease the disease index. Therefore, understanding how the phylloplane defense acts in the fungal spore germination process is essential to develop pre-infection control strategies for cacao plants against witches' broom.